Geotechnical Assessment of the Slopes of Hamamok Dam, NE of Koya, Kurdistan Region of Iraq - Ghafour, Bahra Dh.; Hamawandy, Mohammed J.; Sissakian, Varoujan K. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
The Hamamok Dam is an earthfill dam with a height of 25 m and length of 125 m; constructed in 2011; located northwest of Koya town on a deep canyon-like valley that flows along the southeastern plunge of the Bana Bawi anticline; which forms Bawagi Mountain. The exposed rocks in the site belong to the Pila Spi and Gercus formations; however, rocks of the Khurmala and Kolosh formations are exposed upstream from the dam’s reservoir. The difference in the hardness of the carbonate rocks of the Pila Spi Formation which forms the uppermost parts of the cliffs surrounding the dam site and those of soft reddish brown clastics of the Gercus Formation caused steep slopes that suffer from slope instability problems. To assess a geotechnical study of slopes in the dam site, we have collected different field data to perform a Kinematic assessment method using Dip Analyst 2.0 software and draw the stereographic projection for the studied 10 stations using Stereonet v.11 software. Besides Bejerman’s method, which is based on field data only and indicates the Landslide Possibility Index (LPI). The results showed that the L.P.I. values range between 23 and 27, whereas the results of the Kinematic analysis showed that the right bank (Stations 1 – 5) suffers from plane sliding, whereas the left bank (Stations 6 – 10) suffers from toppling. In both cases, Joint 2 has the main role in the developed failures.